Work engagement versus workaholism: a test of the spillover‐crossover model. Issue 1 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this study is to examine how two different types of heavy work investment – work engagement and workaholism – are related to family satisfaction as reported by employees and their intimate partner.Design/methodology/approach – In total, 398 Japanese couples completed self‐reported questionnaires including the model variables. One year later, participants reported again on their family satisfaction. Structural equation modelling analyses were used to test the hypotheses.Findings – As hypothesized, work engagement was positively related to work‐family facilitation, which, in turn, predicted own and partner's family satisfaction, also one year later. In contrast, workaholism showed a positive relationship with work‐family conflict, and had an indirect negative effect on own and partner's family satisfaction. The structural relationships between the variables from husbands to wives were similar to those from wives to husbands.Research limitations/implications – The use of a non‐experimental design does not allow for definitive conclusions regarding causality.Practical implications – The findings contribute to the work‐family interface literature by showing how experiences built up at work can have a positive or negative impact on one's partner's family satisfaction. The study highlights a growing need to promote work engagement and discourage workaholism within organizations since engagement has positive and workaholism has negative implications for employees' private life.Originality/value – This study clearly shows the differences between two important work experiences – work engagement and workaholism. Using the spillover‐crossover model, the study sheds a new light on the process through which employee work engagement and workaholism influence one's partner at home.